Additive manufacturing of polymer moulds for small-batch injection moulding - Godec, Damir; Breški, Tomislav; Katalenić, Miodrag (2020)
In case of small-batch production, applications of classic technologies and tools, for e.g. injection moulding and classic moulds are not competitive. Application of additive technologies (AT) for direct production of finally parts can partially reduce deficiencies of classic approach, but there are for e.g. limited number of available materials. Potential solution is application of AT in production of so called bridge moulds for small-batch production from originally requested material for final part. This paper presents PolyJet process of AT and its possible application for production of bridge polymer moulds for injection moulding of small quantity of the moulded parts together with design rules for PolyJet bridge moulds.
Bibliografija: 15 jed.
Abstract.
Keywords: Polimeri -- Polimerni kalupi -- Injekcijsko prešanje -- 3D printanje